Perbandingan Kinerja Perkebunan Kelapa Sawit Indonesia dan Malaysia - M Hudori (JURNAL CITRA WIDYA EDUKASI, 2017)
This research will discusses the comparative performance of palm oil plantations in Indonesia and Malaysia. As a major supplier of crude palm oil (CPO) in the world, Indonesia and Malaysia continue to develop palm oil plantation management system. The management system is done will determine the performance of the industry. This research was conducted based on data macro from industry palm oil plantations in Indonesia and Malaysia. The performance will be compared is the growth of the planting area, the harvested area, CPO production, land productivity, domestic consumption, export of CPO and CPO price in the international market during the period 2000 – 2015. The data processing is done by mathematical methods and the results will be analyzed analytical-descriptive. The results showed that the performance of the development of planted area, harvested area and export of CPO, Indonesia is better than Malaysia, while the growth performance of domestic consumption, land productivity and the CPO price in the international market, Malaysia is better than Indonesia.